POST HARVEST LOSS IN RICE PRODUCTION: EVIDENCE FROM A RURAL COMMUNITY IN NORTHERN NIGERIA - Ibrahim, H. I.; Saba, S. S.; Ojoko, E. A. (FUDMA Journal of Sciences, 2023)
Rice is a major food crop in Nigeria but the supply of the crop is constrained by several factors such as Post harvest loss (PHL). PHL constitutes a threat to household food and nutrition security as it leads to reduction in both quality and quantity of household food production. This study was conducted to increase our understanding of the menace with a view to proffering lasting solutions. Using primary data collected from a village survey of 100 Rice farmers in Niger State, we determined the stages, causes, quantity and value of PHL in rice. We found that the major stages of PHL were at harvesting and postharvest handling, point of processing, at storage, and during transportation to place of storage or marketing. PHL was higher with paddy rice and occurred mostly during harvesting while the losses for milled rice occurred mostly during storage. The causes at various stages were due to spillage, breakage due to over drying, rodent attack, theft, and spillage due to poor packaging materials used during transportation. Based on findings from the study, we conclude that Postharvest loss especially in paddy rice, has proved to be a threat to rice production and household food security. We recommend that the state agricultural extension service should enlighten farmers on proper postharvest handling methods for rice. The provision of modern processing and storage facilities such as rice destoners, metal silos and Purdue Improved Crop Storage by government and NGOs at subsidised rates can help to reduce PHL in rice